In Conversation with Rabindranath (Journal of Parents and Teachers, 2025)
The article highlights the importance of poets, as they are the ones who understand the language of things. They are the chosen ones of God, who convey human warmth and either bless or curse humanity. Additionally, it lists a series of affirmations and exclamatory phrases that Tagore sought to express.